SOCIAL MEDIA ANALYTICS FOR BUSINESS DECISION MAKING (CAHIERS MAGELLANES-NS, 2024)
This essay examines the evolution, user demographics, and advantages of social media. Many social media platforms are now effectively utilized, with their data aiding in uncovering hidden insights through analysis. In the realm of social computational science, which supports decision-making, data analysis holds paramount importance. Known as social media data analytics or simply social media analytics, big data analytics on social media offers analysts significant opportunities to develop innovative concepts and identify emerging patterns. This study also explores various forms of social media analysis and commonly employed technologies for social media analytics, along with the numerous research challenges associated with studying social media.To discern patterns, trends, and insights within the collected data, a variety of statistical and machine learning techniques are utilized. These include sentiment analysis, network analysis, text analysis, and machine learning algorithms. Additionally, data visualization plays a crucial role in presenting the analyzed data in a visually appealing and understandable manner, utilizing graphs, charts, and other visual aids.The benefits of social media analytics encompass enhancing overall business performance, increasing consumer engagement, raising brand awareness, identifying market trends, and enhancing customer service. Businesses that heavily rely on social media for customer outreach and brand promotion can particularly benefit from social media analytics. Through the analysis of social media data, businesses can identify their target audience, evaluate the effectiveness of their social media endeavors, and make data-driven decisions.In conclusion, social media analytics serves as a valuable tool for businesses to gain insights and make informed decisions based on social media data. With the right tools and strategies, businesses can leverage social media analytics to enhance consumer engagement, boost brand awareness, and ultimately improve overall business performance.